Efficiency and determinants of profitability of the banks in Vietnam - Phan, Viet Hoang (2015)
This study aims to estimate the X-efficiency scores as well as find out the determinants of profitability of Vietnamese banks during the period 2007 – 2013. With the use of accounting data of 36 commercial banks, two methods were carried out: Stochastic Frontier Analysis and System Generalized Method of Moments. X-effciency scores were obtained from SFA, and then included in s-GMM model as an independent variable. X-efficiency scores of Vietnamese commercial banks in the period 2007 – 2013 were found to be 86% on average. Results from s-GMM estimation suggest that banks should rely on both internal and external factors as well as efficiency scores to improve their profitability.